Building resilience in the face of adversity: navigation processes used by older lesbian, gay, bisexual and transgender adults living in Ireland. Issue 23 (9th June 2016) - Higgins, Agnes; Sharek, Danika; Glacken, Michele
Abstract : Aims and objectives: To explore resilience processes among older lesbian, gay, bisexual and transgender adults. Background: Older lesbian, gay, bisexual and transgender identities have frequently been viewed from a deficit, vulnerability and pathological perspective; consequently, the natural resilience processes that underpin the lives of many older lesbian, gay, bisexual and transgender people goes unrecognised, with few studies focusing on the processes they use in building resilience. Design: The design of the study is qualitative and exploratory. Methods: Data were collected through in‐depth, face‐to‐face interviews. Thirty‐six lesbian, gay, bisexual and transgender people participated in the interviews. The mean age of the interview participants was 60·3 years. Thematic analysis was used to analyse the data. Results: Nine processes were identified that enhanced participants resilience, namely: 'Making a decision to accept oneself and not be defined by lesbian, gay, bisexual and transgender identity'; 'Acquiring an empowering perspective'; 'Learning to let go and moving on'; 'Leaving oppressive social environments'; 'Experiencing affirming relationships with family and others'; 'Accessing formal supports'; 'Maintaining connections with lesbian, gay, bisexual, and transgender people'; 'Remaining positive and being thankful for life' and 'Remaining active and keeping busy'. These processes fostered the development of characteristics, such as: courage and strength; a positive sense of self and an optimistic outlook on life. Conclusion: This study provides evidence of the considerable strength among this group of people, highlighting how adversity has engendered in participants a set of resilience skills, adding to the emerging body of research into resilience and older lesbian, gay, bisexual and transgender people. Relevance to clinical practice: Nurses not only need to be aware of the life histories of older lesbian, gay, bisexual and transgender people but they also need to assess their strengths and offer sensitive services that promote and support resilience among this population.